A longitudinal study of schistosome intermediate host snail populations and their trematode infection in certain areas of Egypt - Ahmed, Amer; Ruppel, Andreas; Ramzy, Reda (Journal of the Egyptian Society of Parasitology, 2003)
Seasonal variation of Biomphalaria alexandrina and Bulinus truncatus populations and their infection rates with schistosome and other trematode cercariae were studied longitudinally in four water courses located in Giza and Faiyoum Governorates. Abundance of both species varied from year to year and according to the type of habitat. The mean prevalence of Schistosoma mansoni in Biomphalaria was 0.29%, that of S. haematobium in Bulinus was 1.36%. Seasonal variations of age structure of the 2 vector snails were monitored throughout the survey period. Infection rates with schistosome and other trematodes among Bulinus and Biomphalaria increased with the increase in snail size. Data suggest the occurrence of an antagonistic interaction between schistosome and non-human cercariae, especially echinostome, in infected snails.
Gesehen am 14.04.2021